PENGARUH IKLIM DAN KOMITMEN ORGANISASI TERHADAP KINERJA KARYAWAN (KASUS KARYAWAN PT. MITRA WAHYU PRAKASA CABANG PEKANBARU) - Rillah Hayati; Ruzikna " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
This research aims to determine the effect of climate and organizational commitment to employee performance in PT. Mitra Wahyu Prakasa Pekanbaru. Organizational climate as a variable (X1) organizational commitment as a variable (X2) and employee perfomence as a variable (Y). The method of this research was descriptive and quantitative with using SPSS program. The sample used in this research was employee of PT. Mitra Wahyu Prakasa Pekanbaru by respondents as many as 36 people. To determine the number of sample used slovin formula. Sampling technique with census. Data collection through questionnaire and interview. The results analysis used multiple linear regression, t test and f test to know that the variable organizational climate had positive effect toward employee performance, the provision of organizational commitment significantly influence toward employee performance, and significan tinfluence between climate and organizational commitment toward employee performance.Keywords : organizational climate, organizational commitment and employee performance.